Pengaruh Literasi Keuangan dan Sikap Keuangan terhadap Perilaku Pengelolaan Keuangan Mahasiswa - Maria Florensa; Andreas Rengga; Konstantinus Pati Sanga (Jurnal Mutiara Ilmu Akuntansi, 2024)
This research aims to analyze the influence of Financial Literacy and Financial Attitudes on the Financial Management Behavior of Accounting Students, Faculty of Economics and Business, Nusa Nipa University. This type of research is quantitative research with an associative approach. The sampling technique uses probability sampling, a type of Stratified random sampling method, where the sample is determined and determined randomly by dividing the population into several sub-classes and semesters with a sample size of 84 people. The data collection technique used a questionnaire (google form) which was distributed to 84 respondents. Data analysis used multiple linear regression analysis using the Statistical Package for the Social Sciences (SPSS) version 25. The results of this study showed that partially the sig. of financial literacy is 0.000 < 0.05 with a calculated t value of 3.814, Sig. of financial attitude is 0.008 < 0.05 with a calculated t value of 2.703 and simultaneously the sig value from the F test shows that the sig value. from the test is 0.000 < 0.05 with a calculated F of 16.010, so it is concluded that partially or simultaneously Financial Literacy and Financial Attitudes have a significant effect on Student Financial Management Behavior.